Regulation of technology transfer in the European Union and Turkey - Özoğuz, Ayşe Selin (My University, 2004)
The concepts of technology and its transfer gained importance after the globalisation of the world economy. Technology and knowledge are the main drivers of economy today. Therefore, the regulation of technology transfer throughout the world became a crucial issue. In exploring the issue of technology transfer, the concept of innovation comes to the forefront. Namely, innovation offers new goods, new services or new production processes and triggers dynamism and growth of the economy. Two important areas of law play a crucial role in the exploration of innovation. These are firstly intellectual property rights (IPRs) and secondly competition law. IPRs provide incentives for innovative efforts and their dissemination and commercialisation by establishing enforceable property rights for the creators and producers of new and useful products, more efficient processes and original works of expression. Competition law promotes innovation and consumer welfare by prohibiting certain actions that may harm competition. Although, both IPRs and competition law are directed towards the same purposes of promoting innovation and consumer welfare, their different ways of achieving their objectives puts them in opposition as well. The regulation of technology transfer is a way of balancing these interests. Therefore the question that is explored in this study is what level of IP protection is sufficient to create a substantial incentive to innovate, without creating rights to exclude so broad as to impair competition. The aim of this study is to explore the subject of technology transfer and its regulation, with a scope covering mainly the law in the European Union (EU) and in Turkey. First the concept of innovation is explored. The purposes of IPRs and competition law are explained and their relationships with innovation are elaborated. Then the conflicting issues of IPRs and competition law are demonstrated, by references to the EU law on this subject. Before exploration of the regulation of technology transfer, the concept of technology transfer and the differences of the developed countries and developing countries are given in order to understand the standpoint of Turkey with respect to technology transfer and its formation. The technology transfer regulations and the experiences in their shaping in the EU are illustrated. Before elaborating the situation in Turkey, policy suggestions on how to absorb the transferred technology are given. The legal situation in Turkey is illustrated by referring to various opinions on the subject and to the relevant existing laws and cases.

Teknoloji ve teknoloji transferi kavramları dünya ekonomisinin globalleşmesinden sonra son derece önem kazanmıştır. Bugünün ekonomisini teknoloji ve bilgi yapılandırmaktadır. Bu yüzden tüm dünyada teknoloji transferinin regülasyonu önem kazanmıştır. Teknoloji transferi konusu irdelenirken, teknolojik yenilik (inovasyon) kavramı öne çıkmaktadır. Zira, teknolojik yenilikler dah iyi ve yeni mal ve hizmet sunulmasını, daha iyi ve yeni süreçlerin geliştirilmesini sağlayarak, ekonomiye dinamizm getirir ve ekonomik büyümeye katkıda bulunur. Teknolojik yenilikten bahsettiğimizde, iki önemli hukuk alanı rol oynamaktadır. Bunlardan birincisi fikri ve sınai mülkiyet hakları (FSMH) hukuku, diğeri ise rekabet hukukudur. FSMH, sahibine özel haklar tanıyarak teknolojik yeniliklerin oluşumunu ve bunların yayılmasını teşvik eder. Rekabet hukuku ise pazarda rekabeti bozan her türlü fiili engelleyerek, rekabetin sağlıklı işleyişşini kontrol eder ve böylelikle tüketiciye yarar sağlar. FSMH ve rekabet hukukunun amaçları teknolojik yeniliklerin teşviki ve böylelikle tüketiciye yarar sağlamaları konusunda birleşmektedir. Ancak bu amaçlarını gerçekleştirirken farklı yollar kullanıyor olmaları onları karşı karşıya da getirebilmektedir. Teknoloji transferinin regülasyonunun amacı bu farklılıkları dengede tutmaktır. Bu yüzden önümüzdeki çalışmada incelenen konu FSMH'nın, pazardaki rekabetin engellenmesine izin verilmeden, hangi seviyede korunabilir olması gerektiğidir. Bu çalışmanın amacı teknoloji transferi ve regülasyonunu irdelemektir. Çalışmanın kapsamı Avrupa Birliği (AB) ve Türkiye'dir. Öncelikle teknojik yenilik kavramı üzerinde durulmaktadır. FSMH hukuku ve rekabet hukukunun amacı ve bu hukuk dallarının teknolojik yenilikle olan ilişkilerine açıklık getirilmektedir. Daha sonra bu iki hukuk dalının çatıştığı noktalar, konuyla ilgili AB hukukundaki değerlendirmelere değinilerek gösterilmektedir. AB hukukundaki teknoloji transferi regülasyonlarına geçilmeden önce Türkiye'nin teknoloji transferi regülasyonu konusundaki konumu ve buna göre yapılması gereken çalışmalara ışık tutmak amacıyla, teknoloji transferi kavramı ve bunun gelişmiş ülkeler ve gelişmekte olan ülkelerdeki farklılıkları üzerinde durulmaktadır. AB hukukundaki teknoloji transferi regülasyonları, bunların oluşumları ve değerlendirmeleri gösterilmektedir. Türkiye'deki durum irdelenmeden önce, gelişmekte olan ülkelerde teknoloji transferinin nasıl adapte edilmesi gerektiği konusuna değinilmektedir. Türkiye'deki hukuki durum farklı görüşlere, kanunlara ve bu konudaki davalara yer verilerek incelenmiştir.
Keywords: Teknoloji Transferi